Manajemen Pengendalian Waktu Dan Biaya Pada Proyek Daerah Irigasi Saluran Primer Ketonggo Dengan Menggunakan Metode Pert - Mohammad Arif Bahtiar Efendi (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2024)
This thesis presents the results of research about time and cost control management in Ketonggo Primary Canal Irrigation Area project. Time and cost in the best planning is needed in project implementation to ensure that project implementation can achieve maximum results by utilizing existing resources. This study uses the PERT (Program Evaluation and Review Technique) method. By implementing Network planning which is one of the management techniques to plan and control the implementation of a project. Optimization needs to shorten the duration of the project with minimal expenditure. Total of this contract is Rp. 4,706,045,953.00 with 90 days of completion. The results of this analysis showed that the most likely project completion time was 90 days, with the fastest being 75 days and the slowest being 105 days. Based on the critical path analysis, obtained 9 work items that are very influential in the smooth running of the project. The optimal project cost at normal time is Rp. 4,249,989,942.19 and the total cost required for project acceleration is Rp. 4,710,928,986. Additional costs are used for additional manpower, additional working hours and additional hours of heavy equipment.